Water Resources and Sustainable Development (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Reprint is designed to serve as a platform for researchers, policymakers, and practitioners to disseminate their most recent findings, innovative ideas, and effective strategies to address the critical issue of water security. This volume encompasses sixteen chapters, organized into four principal thematic areas: Hydrochemical Characteristics and Water Quality, Impact of Human Activities on Water Resources, Water Management Strategies, and Technological Applications for Water Resource Management. By amalgamating a diverse range of studies across various geographical and contextual backgrounds, this Reprint provides a sweeping overview of the current state of water resource management and its pivotal role in sustainable development.